Many People, Many Ways Understanding Cultures around the World. Volume 1 - Brewer, Chris, Comp.; Grinde, Linda, Comp. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1995)
This book helps students and teachers explore the concept of culture and to appreciate the diversity of cultures of the world. The nine cultures in the book represent a variety of races and environments. Each chapter offers ideas for activities for student to explore elements of culture and common human experiences. The chapters are divided into categories to facilitate an interdisciplinary approach with activities designed to address multiple intelligences. Cultures highlighted include: (1) Brazil; (2) Egypt; (3) Haiti; (4) Hawai'i; (5) The Lakota, Dakota, Nakota; (6) Poland; (7) Sweden; (8)Tibet; and (9) Vietnam. An appendix that features a discussion about biomes and a bibliography that includes general references as well a recordings, videos, children's books, teacher works, organizations, and audio cassettes conclude this document. (EH)
ERIC Note: This document is no longer available from the publisher, Zephyr Press.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cross Cultural Studies; Cultural Interrelationships; Cultural Pluralism; Culture; Elementary Education; Ethnology; Foreign Countries; Global Education; Multicultural Education; Social Studies; Asia -- Caribbean -- Europe -- South America; Books; Guides, Non-Classroom.